A new species of Tinna (Hemiptera: Heteroptera: Reduviidae) from Nigeria - Fent, Meral; Dursun, Ahmet (Zootaxa, 2021)
Tinna schoenitzeri sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae: Leistarchini) is described from Nigeria. Digital macrophotographs and scanning electron micrographs of the new species are given.